1975
DOI: 10.1111/j.1464-410x.1975.tb04002.x
|View full text |Cite
|
Sign up to set email alerts
|

The Urodynamic Assessment of Adult Enuresis

Abstract: Urodynamic analysis has revealed a high proportion of uninhibited bladder activity in adult enuresis. There was no associated neurological deficit to explain this abnormality. There was no correlation between the various diurnal symptoms and the presence of uninhibited bladder contractions. Enuresis was associated with obstructive uropathy in only 6 percent of cases. Some evidence has also been presented to support the concepts of ectopic sensory receptors and abnormal sphincter inhibition. A review of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
20
0
1

Year Published

1983
1983
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 12 publications
4
20
0
1
Order By: Relevance
“…In this study, over half of the enuretic children had significantly thickened bladder wall (Ͼ0.5 cm). Bladder wall thickness could be one of the features of detrusor immaturity as suggested in previous studies (13,19,31). This was further supported by the strong association found between thickened bladder wall with high detrusor pressure, unstable bladder contraction, and dyssynergia in this study.…”
supporting
confidence: 77%
See 3 more Smart Citations
“…In this study, over half of the enuretic children had significantly thickened bladder wall (Ͼ0.5 cm). Bladder wall thickness could be one of the features of detrusor immaturity as suggested in previous studies (13,19,31). This was further supported by the strong association found between thickened bladder wall with high detrusor pressure, unstable bladder contraction, and dyssynergia in this study.…”
supporting
confidence: 77%
“…A number of studies have suggested presence of detrusor overactivity in enuretics (7,13,28). Watanabe and Azuma (29) found enuretics had more unstable contractions at night than at daytime.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…During daytime, such disturbance might cause a late occurrence of the desire to void, 'late warning hypesthetic urgency' [10]. Others [11][12][13] described that in patients with bed-wet ting a pathological tension-reception might exist which might in turn be responsible for a deficient sensory stimu lation during sleep.…”
Section: Sensation Of Lower Urinary Tract Inmentioning
confidence: 99%